El Trabajo Infantil en los Sectores Informales y la Protección Integral del Niño en la Constitución de la República del Ecuador y en el Código de la Niñez y Adolescencia - Vera Donoso, Nidia Maritza (2017)
One of the goals of this research is focused on the protection of children and adolescents who work in the informal sectors, the lack of a regulation or law has ceased as a result a very sensitive social issue in view of our social environment, most children who develop these activities do in order to generate income to supplement the family budget, is a population of less clear magnitude is but broken family ties, and has been forced to live practically on the Street. Children working on the street, provide a livelihood and support their families in order to access a new way of life not so lacking needs. Therefore their presence on the streets is one of the most obvious manifestations of the lack of capacity of a system that cares little about the rights of this vulnerable sector. This sector should be protected by the state, establish greater protection for them to feel safer when performing these tasks. In addition, various concepts are established that tend to relate to the child, refers to all those artisan economic activities such as peddling market sales that operate from the resources of households, but without forming as companies. History shows clearly that the poor have only put their children to work when they themselves have had no other resource for survival than the sale of their labor power; That is, when they were already poor, they found themselves reduced to absolute misery. In the doctrinal framework, society 5 should be concerned with demanding and demanding that children's institutions take action when children are in danger, and not only when it is a danger, for it is essential a real policy that places within their priorities A control in this sector that today is unprotected, in any case the legal framework regarding the regulations of the Constitution of Ecuador speaks of equality of rights without any discrimination, therefore it is the State that must ensure the protection and Welfare of minors.